Komparasi Strategi Relationship Marketing Dan Pelayanan Prima Dengan Strategi Peningkatan Fee - Fajar Suryatama; Suhaji Suhaji (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
This study tested the 2 (two) corporate strategy funding, PT Adira DMF Relathionship with strategy and excellent service while its competitors, PT. Suzuki Finance Indonesia uses the strategy of Fee. This research seeks answers to whether the granting Fee factors other than in the form of cash, is there any other factors that may affect the decision of the dealer to give order to the Financing Institution. The results of this research is the Relationship Marketing strategy and excellent service can affect the decision of granting the order to the Institution by denying Financing amount of Fee is received.